1992
DOI: 10.1366/0003702924125690
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Concentration Profiles of Additives in Polymers by IR Microspectroscopy: The Diffusion of Cyasorb UV531 in Polypropylene

Abstract: The recent advancement in FT-IR microspectrometry has provided a convenient way to probe the concentration profiles of additives in polymers. This technique opens up intriguing prospects for investigating additive/polymer or polymer/polymer interaction. In this work, the diffusion of a UV stabilizer, UV531, in polypropylene was selected to illustrate the applications of an IR microscope to monitor the concentration profiles of additives in polymers. In addition, a nonlinear least-squares fitting program was wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Hsu et al reported on the use of FT-IR microspectroscopy (FT-IR/ mS) to map the concentration pro le of a UV stabilizer in 520-mm-thick polypropylene plaques. 16 In their experiments, they placed powdered stabilizer in contact with a neat plaque, allowed the stabilizer to diffuse into the plaque for a prescribed period of time, and then calculated the additive diffusivity based on the measured concentration pro le. In contrast to those mass-sorption (or ''diffusion in'') experiments, we wanted to track the proles of additive diffusing out of the polymer, which mimics the behavior in comm ercial lm.…”
Section: Introductionmentioning
confidence: 99%
“…Hsu et al reported on the use of FT-IR microspectroscopy (FT-IR/ mS) to map the concentration pro le of a UV stabilizer in 520-mm-thick polypropylene plaques. 16 In their experiments, they placed powdered stabilizer in contact with a neat plaque, allowed the stabilizer to diffuse into the plaque for a prescribed period of time, and then calculated the additive diffusivity based on the measured concentration pro le. In contrast to those mass-sorption (or ''diffusion in'') experiments, we wanted to track the proles of additive diffusing out of the polymer, which mimics the behavior in comm ercial lm.…”
Section: Introductionmentioning
confidence: 99%
“…A technique that has been used successfully to map concentration profiles in thicker films is known as FTIR microspectroscopy (FTIR-mS). In this method, a specimen is microtomed, mounted in a microcompression cell, and placed on a microscope stage such that one sees an endview of the film [4][5][6][7]. The microscope's aperture system and objective are then used to focus the infrared beam on the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…However, the focus of our research is on the use of FT-IR m icrospectroscopy (FT-IR-m S) 7±9 to map the concentration pro® le of an erucamide slip agent in linear low-density polyethylene (LLDPE). Hsu et al 10 reported the use of this technique to m easure the extent to which a UV stabilizer penetrated into initially additive-free plaques of polypropylene (so-called``diffusion in' ' studies). From their results, Hsu et al were able to calculate diffusion coef® cients.…”
Section: Introductionmentioning
confidence: 99%